Unformatted text preview:

More ProofsDr. HolmesSeptember 4, 20091 Summary of Proof Strategies1.1 Basic Logical Conceptscontradiction: I’m introducing a symbol ⊥ for a sentence which is false,read “contradiction”.negation: If P is a sentence, ¬P means “It is not the case that P ”, “P isfalse”, “not P ”.conjunction: If P and Q are sentences, P ∧ Q means “P and Q”.disjunction: If P and Q are sentences, P ∨ Q means “P or Q (or both)”.This is the default meaning of “or” in mathematical English.implication: If P and Q are sentences, P → Q is read “if P then Q” or“P implies Q”. This is understood to be false only if P is true andQ is false: it is exactly equivalent to ¬(P ∧ ¬Q) or to ¬P ∨ Q. Thisis the default meaning of “if. . .then. . .” or “implies” in mathematicalEnglish.biconditional: If P and Q are sentences, P ↔ Q means “P if and only ifQ”, or “P implies Q and Q implies P ”. This is abbreviated “P iff Q00.universal quantifier: (∀x.P (x)) means “for all x, P (x)” and (∀x ∈ A.P (x))means “for all x in the set A, P (x)”.existential quantifier: (∃x.P (x)) means “for some x, P (x)” or “there ex-ists an x such that P (x), and (∀x ∈ A.P (x)) means “for some x in theset A, P (x)”, or “there exists an x in A such that P (x).11.2 Proving sentences of these formsIn this subsection we have techniques for proving statements of each of theselogical forms, and sample outlines of what such a proof (in a highly formalizedstyle) would look like.contradiction: To prove ⊥, prove A and prove ¬A (for some sentence A) [wecertainly hope that we cannot do this except under bad assumptions!]negation: To prove ¬A, assume A and prove ⊥ (which you can only do byproving some B and ¬B).Goal: ¬AAssume: AGoal: contradiction[proof of B][proof of ¬B]completing a contradiction: B might be any statement.conjunction: To prove P ∧ Q, prove P , then prove Q.Goal: P ∧ QGoal 1: P[proof of P ]Goal 2: Q[proof of Q]Notice that the single conjunction goal unpacks into two goals whicheach need to be proved separately.disjunction: To prove P ∨ Q, do one of four things (you do not need to domore than one!):Method 1: Assume ¬P (for the sake of argument) then prove Q; whendone with this proof of Q, one no longer can use the assumption¬P , which is local to that proof.Goal: P ∨ QAssume: ¬P2Goal: Q[proof of Q]Notice that the assumption ¬P and any conclusion proved using¬P (including the local conclusion Q) can only be used in theindented part of the proof.Method 2: Assume ¬Q (for the sake of argument) then prove P ; whendone with this proof of P , one no longer can use the assumption¬Q, as above.Goal: P ∨ QAssume: ¬QGoal: P[proof of P ]Notice that the assumption ¬Q and any conclusion proved using¬Q (including the local conclusion P ) can only be used in theindented part of the proof.Method 3: Notice that it is enough just to prove P .Goal: P ∨ QGoal: P[proof of P ]Method 4: Notice that it is enough just to prove Q.Goal: P ∨ QGoal: Q[proof of Q]implication: To prove P → Q, assume P (for the sake of argument), thenprove Q. The assumption P can only be used in this local proof of Q.Goal: P → QAssume: PGoal: Q[proof of Q]The assumption P and anything proved using it can only be used inthe indented part of the proof.3An alternative strategy (proof by contrapositive) is to assume ¬Q andthen prove ¬P .Goal: P → QAssume: ¬QGoal: ¬P[proof of ¬P ]biconditional: To prove P ↔ Q one needs a proof with two parts: in thefirst part one assumes P for the sake of argument then proves Q; in thesecond part one assumes Q for the sake of argument then proves P .Goal: P ↔ QPart 1: Assume: PGoal: Q[proof of Q]Part 2: Assume: QGoal: P[proof of P ]One or both of the embedded proofs of P → Q and Q → P could bereplaced with proofs by contrapositive.universal quantifier: To prove (∀x.P (x)), introduce an arbitrary object a(about which we may make no special assumptions; we should not haveever mentioned it before), and prove P (a). After the end of this proofwe should not refer to this a again.To prove (∀x ∈ A.P (x)), introduce an arbitrary object a (about whichwe may make no special assumptions; we should not have ever men-tioned it before), assume a ∈ A and prove P (a). After the end of thisproof we should not refer to this a again.existential quantifier: To prove (∃x.P (x)), find an object t such that youcan prove P (t).To prove (∃x ∈ A.P (x)), find an object t such that you can prove t ∈ Aand you can prove P (t).4proof by contradiction: To prove any statement A at all: assume ¬A anddeduce a contradiction.Goal: AAssume: ¬AGoal: contradiction[proof of B][proof of ¬B]where B can be any statement.1.3 Using theorems, assumptions or conclusions of theseformscontradiction: If you have assumed or concluded ⊥, you may assume orconclude any further conclusion A that you want (a false statementimplies anything).negation: If you have assumed or concluded ¬¬A, you may conclude A.The main use of a negative conclusion ¬A is to see if you can also proveA and thus prove a contradiction (⊥).Here is a proof fragment where a negative hyp ¬A is used in this way.¬AGoal: ¬BAssume: BGoal: contradictionGoal: A (for the sake of a contradiction)[proof of A](the point is that we now have a contradiction because¬A is already a conclusion above)conjunction: If you have assumed or concluded P ∧ Q, you may also con-clude P and you may also conclude Q.5disjunction: If you have assumed or concluded P ∨ Q and are trying toprove G, you can complete the proof using proof by cases: (case 1)assume P , then prove G; (case 2) assume Q, then prove G.Here is a bit of proof text:P ∨ QGoal: GCase 1: Assume: PGoal: G[proof of G]Case 2: Assume: QGoal: G[proof of G]implication: If you have assumed or concluded P → Q, and have alsoassumed or concluded P , you can further conclude Q (rule of modusponens).(1) P → Q(2) PQ, from (1) (2) by the rule of modus ponensIf you have assumed or concluded P → Q, and have also assumed orconcluded ¬Q, then you can further conclude ¬P . (modus tollens)(1) P → Q(2) ¬Q¬P , from (1) (2) by the rule of modus tollensIf you have just the assumption or conclusion P → Q and it is unclearwhat to do next, try proving P (because if you do you can furtherconclude Q), or proving ¬Q (because if you do you can further conclude¬P ).Here is a proof fragment:A → BGoal: G . . .6Goal: A (for the sake of


View Full Document

BOISE STATE MATH 314 - More Proofs

Download More Proofs
Our administrator received your request to download this document. We will send you the file to your email shortly.
Loading Unlocking...
Login

Join to view More Proofs and access 3M+ class-specific study document.

or
We will never post anything without your permission.
Don't have an account?
Sign Up

Join to view More Proofs 2 2 and access 3M+ class-specific study document.

or

By creating an account you agree to our Privacy Policy and Terms Of Use

Already a member?